O discurso bolsonarista nas redes sociais: uma análise dos limites da liberdade de expressão - Dzwielewski, Kellin (2024)
The production of discourse, in any society, is regulated and shaped by a series of events. In a context where hate speech and misinformation proliferate on social networks, it is necessary to discuss the impact of the dissemination of sayings on the internet. Thus, the general objective of this research was to analyze the relationship between the Bolsonarist discourse on social networks and the concepts of free speech. Furthermore, the study examined the contours, meanings and limits of free speech when this speech puts other fundamental rights in a society at risk. As a methodology, bibliographical research of a qualitative-interpretative nature was used, whose categorization and data analysis were based on Orlandi's Discourse Analysis (2005). For this, posts and comments from Bolsonaro and his supporters were selected, extracted through publications on social networks X (formerly Twitter), Facebook and YouTube videos reproduced and multiplied by online newspapers. Furthermore, national and international legal standards were used, such as: Federal Constitution of Brazil of 1988 (Brasil, 1988); United Nations (UN) with the text Pacto Internacional de Derechos Civiles y Políticos, article 19, year 1948 (United Nations, 2011); and the 1969 American Convention on Human Rights, article 13 (Organization of American States, 2024). The main period of analysis covered the years 2018 to 2022, however, at times, statements before 2018 and after 2022 were included, due to the need to complement the study. Among the results, we can verify that the speeches analyzed demonstrate the obstacles that free speech faces in the era of social media and in current politics. Although generally recognized as one of the main pillars of democracy, free speech often proved to be, when observed in Bolsonaro's discourse, an instrument of legitimacy for the dissemination of predatory speeches, which go beyond the limits accepted by the legislation, especially when they violate other fundamental rights, such as human dignity and equality. It thus ends up establishing a polarized vision, which does not provide opportunities for divergent opinions, weakening democratic structures, in addition to inhibiting plural democracy and peaceful coexistence in society. In this way, the analyzed speeches challenge the notion of unlimited freedom. In this case, an ethical and legal regulatory approach becomes necessary to ensure that the human rights and dignity of every citizen are respected. Maintaining this balance is fundamental for the construction of the Democratic State of Law, which seeks to preserve plural coexistence and respect for human rights.